MINIATURE NATURAL "EXPERIMENT" OF STRUCTURES FORMATION IN SHEAR PLASTIC FLOW OF MIGMATITE PRODUCTS AND ITS COMPARISON WITH LABORATORY MODELING OF VISCOUS LIQUIDS FLOW - Lukiyenko, O.; Кravchenko, D. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Small area (about 200 m2) of high-plastic (to approximate viscous) shear flow have been investigated on the example of the area within Golovanevsk suture zone on the Ukrainian shield. It is a miniature example of wide range small structural forms provided by plastic flow. This tectonic formation has good lateral zonality, which markes tectonic facies from V to X (by ten-unit scale). The general feature of investigated shear zone is the linearization of all structural shapes and bodies, their orderly orientation relative to the direction of displacement. This zone has been qualified as a miniature natural "experiment" of structure formation through plastic shear flow. Therefore, we propose to consider this area as tectonic type of shear structures for pre-Cambrian shear-zones. Natural structural forms demonstrated on investigated area have been compared with similar forms obtained at very slow reverse flow of viscous liquids under laboratory conditions (experiment data used G. Ottino). Our investigation has been determined that viscous liquid structural forms are similar to natural structures. It indicated the similarity of forming mechanisms in nature and physical modeling.